2006
DOI: 10.1016/j.ncl.2006.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine, Sickness Behavior, and Depression

Abstract: SummarySufficient evidence is now available to accept the concept that the brain recognizes cytokines as molecular signals of sickness. Clarifying the way the brain processes information generated by the innate immune system is accompanied by a progressive elucidation of the cellular and molecular components of the intricate system that mediates cytokine-induced sickness behavior. We are still far, however, from understanding the whole. Among the hundreds of genes that proinflammatory cytokines can induce in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
388
0
14

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 414 publications
(415 citation statements)
references
References 90 publications
13
388
0
14
Order By: Relevance
“…The role of both brain and peripheral inflammation as a factor contributing to depression has been supported by clinical and experimental evidence, such as the presence of both brain and peripheral markers of inflammation in major depression patients; high frequency of comorbidity between primary autoimmune disorders and mood impairments; antidepressant effectiveness of anti-inflammatory drugs; the occurrence of clinical symptoms of depression in patients undergoing chemokine immunotherapy; the evolvement of behavioral and neuroendocrine depressive impairments in experimental animals treated with proinflammatory compounds [17,40,41]. Among various factors of inflammation, IL-1β appears to have particularly strong association with depression [17,18,20,42].…”
Section: Il-1ra Monotherapymentioning
confidence: 99%
See 3 more Smart Citations
“…The role of both brain and peripheral inflammation as a factor contributing to depression has been supported by clinical and experimental evidence, such as the presence of both brain and peripheral markers of inflammation in major depression patients; high frequency of comorbidity between primary autoimmune disorders and mood impairments; antidepressant effectiveness of anti-inflammatory drugs; the occurrence of clinical symptoms of depression in patients undergoing chemokine immunotherapy; the evolvement of behavioral and neuroendocrine depressive impairments in experimental animals treated with proinflammatory compounds [17,40,41]. Among various factors of inflammation, IL-1β appears to have particularly strong association with depression [17,18,20,42].…”
Section: Il-1ra Monotherapymentioning
confidence: 99%
“…Among various factors of inflammation, IL-1β appears to have particularly strong association with depression [17,18,20,42]. Recent studies have reported the association between the polymorphism of IL1-β promoter and major depression [43], and they have even implicated IL-β gene polymorphism (specifically its rs16944 variant, which results in the increased IL1-β levels) in the lack of response to SSRI [44].…”
Section: Il-1ra Monotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, multiple studies in both animals and humans have demonstrated that administration of PICs is sufficient to induce the sickness response and conversely that PIC antagonists can block that response [10].…”
Section: Inflammation and Sickness Behaviormentioning
confidence: 99%